2021
DOI: 10.1128/jvi.02336-20
|View full text |Cite
|
Sign up to set email alerts
|

Valosin-Containing Protein/p97 Plays Critical Roles in the Japanese Encephalitis Virus Life Cycle

Abstract: Host factors provide critical support for every aspect of the virus life cycle. We recently identified the valosin-containing protein (VCP)/p97, an abundant cellular ATPase with diverse cellular functions, as a host factor important for Japanese encephalitis virus (JEV) replication. In cultured cells, using siRNA-mediated protein depletion and pharmacological inhibitors, we show that VCP is crucial for replication of three flaviviruses: JEV, Dengue, and West Nile viruses. An FDA-approved VCP inhibitor, CB-5083… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…Recent [53]. Additional characterization indicated that the VCP inhibitor prevented JEV from leaving clathrin-coated vesicles and interfered with capsid protein degradation [53], in agreement with the idea that ATPase activity is required for uncoating of flaviviruses.…”
mentioning
confidence: 54%
See 4 more Smart Citations
“…Recent [53]. Additional characterization indicated that the VCP inhibitor prevented JEV from leaving clathrin-coated vesicles and interfered with capsid protein degradation [53], in agreement with the idea that ATPase activity is required for uncoating of flaviviruses.…”
mentioning
confidence: 54%
“…Furthermore, the role of VCP/p97 is evolutionarily conserved since inhibitors also blocked pre-replication events of YFV in mosquito cells [40]. Recent [53]. Additional characterization indicated that the VCP inhibitor prevented JEV from leaving clathrin-coated vesicles and interfered with capsid protein degradation [53], in agreement with the idea that ATPase activity is required for uncoating of flaviviruses.…”
mentioning
confidence: 63%
See 3 more Smart Citations